2021
DOI: 10.18632/aging.203584
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CD8+ T cell infiltration-related biomarkers and the corresponding prediction model for the prognosis of kidney renal clear cell carcinoma

Abstract: Cytotoxic T cells expressing cell surface CD8 played a key role in anti-cancer immunotherapy, including kidney renal clear cell carcinoma (KIRC). Here we set out to comprehensively analyze and evaluate the significance of CD8 + T cell-related markers for patients with KIRC. We checked immune cell response in KIRC and identified cell type-specific markers and related pathways in the tumor-infiltrating CD8 + T (TIL-CD8T) cells. We used these markers to explore their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…[ 24 , 25 ] Previous studies have raised that CD8T cell infiltration was associated with the results of immunotherapy. [ 26 ] Furthermore, Nalio Ramos et al [ 27 ] have elucidated the impact of CD8T cells on the function of macrophages in breast cancer. Additionally, Bachiller et al [ 28 ] found have discovered that NK cells enhance the tumor-suppressive function of T cells, which suggested that the interaction of immune cells was meaningful for the tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 25 ] Previous studies have raised that CD8T cell infiltration was associated with the results of immunotherapy. [ 26 ] Furthermore, Nalio Ramos et al [ 27 ] have elucidated the impact of CD8T cells on the function of macrophages in breast cancer. Additionally, Bachiller et al [ 28 ] found have discovered that NK cells enhance the tumor-suppressive function of T cells, which suggested that the interaction of immune cells was meaningful for the tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in immunodeficiency pattern patients, improving immune function may be beneficial in terms of prognosis. Numerous studies have found that a dense infiltration of T cells, particularly cytotoxic [ 15 , 16 ], predicts a favorable outcome. However, immune cluster B did not show the expected survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Seven medications that target the VHL signaling pathway have been approved by the Food and Drug Administration (FDA), although data that support their use in improving clinical outcomes and survival in patients with KIRC are limited. [12] Therefore, further research on the development and prognosis prediction of KIRC is warranted to gain deeper insights into its pathogenesis at the molecular level and identify new targets for therapeutic intervention. In recent years, bioinformatics technology has facilitated the development of numerous tools to identify biomarkers.…”
Section: Introductionmentioning
confidence: 99%